Katekis: Pewarta Tersalib ditengah Arus Perubahan Zaman - Kristoforus Kopong, S.Fil., M.Hum (Atma Reksa : Jurnal Pastoral dan Kateketik, 2016)
Catechist is a mere human being called specially to proclaim the Word of God either by wods or by concret every day actions. This implies that the Word of God which is proclaimed by words should be correlated to the life witness a catechist gives in his or her family circumtance as well as in the society or Church’s milieu. This duty becomes heavier as the present human life is strongly invaded by changes of time marked by global trends such as materialism, consumersim, hedonism, individualism, pluralism, fundamentalism, and secularism. Such condition has become for the catechist a special challenge as a messenger or preacher of the Word of God. This is because of the majority of the life choices and orientations of modern mankind are directed to a more attractive offerings than to listening to the teachings given by the catechist. In some cases, even the catchist himself or herself also succumbs to these offerings, which make him or her become less commited to the original vision. This is the cross, means the work and responsibility the catechist should shoulder. That is why, in order that the catechist could stand erect as a crucified witness of the Word, he or she should be attached to three main pillars, which are faith, hope, and love. In the meantime, the catechist should not forget to build an efective and efficient evangelization politics for the realization of vision and mission of the evangelization.